2015
DOI: 10.1111/mmi.13049
|View full text |Cite
|
Sign up to set email alerts
|

Multiple modes of iron uptake by the filamentous, siderophore‐producing cyanobacterium, Anabaena sp. PCC 7120

Abstract: SummaryIron is a member of a small group of nutrients that limits aquatic primary production. Mechanisms for utilizing iron have to be efficient and adapted according to the ecological niche. In respect to iron acquisition cyanobacteria, prokaryotic oxygen evolving photosynthetic organisms can be divided into siderophore-and non-siderophore-producing strains. The results presented in this paper suggest that the situation is far more complex. To understand the bioavailability of different iron substrates and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 63 publications
8
58
2
Order By: Relevance
“…While the α-carboxylate hydroxamate siderophore aerobactin is structurally similar to schizokinen, the tris-hydroxamate DFB is less structurally related (Harris et al 1979;Dhungana et al 2001). It was demonstrated that Fe-DFB is not taken up by SchT, which is consistent with the structural differences of DFB and schizokinen and that uptake across the plasma membrane is mediated by the Fhu system similarly to Fe-schizokinen (Rudolf et al 2015). medium and the cell concentration was adjusted to a final OD 750 of 0.05.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…While the α-carboxylate hydroxamate siderophore aerobactin is structurally similar to schizokinen, the tris-hydroxamate DFB is less structurally related (Harris et al 1979;Dhungana et al 2001). It was demonstrated that Fe-DFB is not taken up by SchT, which is consistent with the structural differences of DFB and schizokinen and that uptake across the plasma membrane is mediated by the Fhu system similarly to Fe-schizokinen (Rudolf et al 2015). medium and the cell concentration was adjusted to a final OD 750 of 0.05.…”
Section: Introductionmentioning
confidence: 80%
“…For uptake experiments cells were treated and collected as described (Rudolf et al 2015). Cells were grown for 3 days in YBG11+10 µM Fe-EDTA as Fe-EDTA cannot be incorporated by cyanobacteria and buffers a constant concentration of bioavailable Fe′ (Kranzler et al 2011).…”
Section: Anabaena Sp Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations